Bubbling Up the Good Ideas: A Two‐Mode Network Analysis of an Intra‐Organizational Idea Challenge. Issue 3 (9th May 2016) - Stephens, Bryan; Chen, Wenhong; Butler, John Sibley
Abstract: Organizations have been experimenting with intraorganizational crowdsourcing (IOC), yet the mechanisms of IOC production remain an underresearched topic. Drawing on a 2‐mode ERGM, we examine structural mechanisms and individual‐level factors that shape the network structure of idea generation and selection yielded by an IOC idea challenge in a global IT corporation. Results show a Matthew effect leading to 1) highly centralized employee participation around a few "superactive" employees who engage with many ideas and 2) highly centralized idea popularity with a few ideas attracting most employee attention. We find support for shared affiliations among employee‐idea clusters in the first half of the participation, which is, however, less likely in the second half. We also find support for geographic homophily.